2019
DOI: 10.1155/2019/6073289
|View full text |Cite
|
Sign up to set email alerts
|

Review of Exogenous Economic Indicators Influencing Construction Industry

Abstract: Research works into the effect of economic factors on the construction industry are enormous. But finding the core economic factors is limited in the Ghanaian construction industry. In an attempt to address this research gap, this study articulates the aim of identifying exogenous economic factors influencing the construction industry through a qualitative literature review. The study used secondary data collected from over 50 published journals, conference papers, and dissertations on exogenous factors. Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
2
12
0
1
Order By: Relevance
“…The proposed methodological approach could be applied in various fields to improve the decision making process. For instance, Asamoah et al (2019) conducted an extensive literature analysis of the economic indicators influencing construction industry. The research identified 59 indicators based on literature analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed methodological approach could be applied in various fields to improve the decision making process. For instance, Asamoah et al (2019) conducted an extensive literature analysis of the economic indicators influencing construction industry. The research identified 59 indicators based on literature analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, real estate analysis is not only limited to price analysis. Asamoah et al (2019) conducted an extensive literature analysis to determine the influence of economic indicators which are important for players in the construction industry including policy makers. The determination of economic factors f the construction industry could reduce the incidence of the high failure rate of construction firms.…”
Section: Introductionmentioning
confidence: 99%
“…Brereton et al (2007) emphasize the necessity of adopting systematic methods to evaluate and aggregate existing research outcomes, as a prerequisite to 'a balanced and objective summary of research evidence for a particular topic' (p. 571). In construction management research, literature reviews are commonly adopted as a form of methodology (Hong and Chan 2014;Osei-Kyei and Chan 2015;Asamoah et al 2019;Odeck 2019). Within the realm of cost overrun research, several studies including Cantarelli et al (2012), Odeck (2004Odeck ( , 2019, and Asamoah et al (2019) have used systematic literature reviews to preview and draw conclusions on specific aspects of the cost overrun literature.…”
Section: Methods Of Studymentioning
confidence: 99%
“…In construction management research, literature reviews are commonly adopted as a form of methodology (Hong and Chan 2014;Osei-Kyei and Chan 2015;Asamoah et al 2019;Odeck 2019). Within the realm of cost overrun research, several studies including Cantarelli et al (2012), Odeck (2004Odeck ( , 2019, and Asamoah et al (2019) have used systematic literature reviews to preview and draw conclusions on specific aspects of the cost overrun literature. Cantarelli et al (2012) as well as Odeck (2004), examined the geographical variability and sizes of cost overrun reported in the literature, while Odeck (2019) and Asamoah et al (2019) focused on their econometric determinants.…”
Section: Methods Of Studymentioning
confidence: 99%
See 1 more Smart Citation